Marshall Loeb's money guide - Loeb, Marshall (Little, Brown and Co, 1983)
According to Marshall Loeb, personal finance covers five ares: earning, investing, saving, spending and enhancing your career. Here, he leads you through these five areas in refreshingly specific terms, telling you whom to call, where to write, which one to buy.